Optimasi Rute Distribusi Biskuit Ubm Menggunakan Metode Saving Matrix untuk Meminimasi Biaya Distribusi pada PT. SJA - Utomo, Edwin Adi; Wati, Putu Eka Dewi Karunia (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT. SJA is a food distributor company located at Jalan Kalianget No.50-52 Surabaya. The main distribution product is UBM biscuits located at Waru, Sidoarjo. The operational costs used in carrying out distribution using the initial route are IDR 25,008,650 for delivery every day. Based on the large costs, a complicated route plan will occur in order to find the minimum costs possible. In optimizing the distribution routes above in order to minimize shipping costs to PT. SJA, a saving matrix method is used. This method can determine product distribution routes to all product marketing areas by determining the route chosen and the capacity of the vehicle used so that the closest route and lowest transportation costs are obtained. Based on the results of the analysis of the research objectives carried out, it can be concluded that the proposed route obtained from processing using the saving matrix method produces differences in terms of costs and transport capacity in March 2024, the company before using this method required shipping costs of IDR 25,008,650 and after using the saving matrix method the company can save costs by 22.34%, namely Rp. 19,421,100